The concept of an individual act as the subject of a public legal dispute - Roi, O.V. (Аналітично-порівняльне правознавство, 2024)
The article is devoted to the study of the issue of the definition of an individual act as the subject of a public-law dispute, which is extremely relevant at the current stage of reforming state institutions and harmonizing the legislation of Ukraine in the process of negotiations on joining the European Union. The article indicates that public-law disputes regarding the appeal of individual acts cover all spheres of the public life of citizens and are a direct consequence of the implementation of publicauthority management functions by subjects of authority. The state of administration of justice by administrative courts in 2020-2023 was studied, and a conclusion was made about the increase in the number of public legal disputes considered by administrative courts. Attention is drawn to the fact that domestic legislation is inconsistent in the field of terminology. In particular, the Law of Ukraine «On Administrative Procedure» uses the concept of «administrative act,» the Code of Administrative Procedure of Ukraine uses the concept of «individual act,» and the Law of Ukraine «On Law-Making Activity» uses «acts application of law,» «other individual legal acts,» and «other legal acts that do not contain legal norms.» In connection with this, subjects of authority often approach issues of terminological apparatus in different ways when processing hundreds of legal acts. In addition, the scientific community does not have a unified approach to this issue, operating with the concepts of «legal acts of state administration», «administrative legal acts», «individual administrative acts», «individual administrative legal acts» and «legal acts of individual action». Taking into account the researched material, it is indicated that most often an individual act is equated with the concept of an administrative act, which is narrower. Therefore, in the context of a public legal dispute, which includes both administrative and judicial appeals, it is appropriate to use the term individual act. It has been concluded that a unified understanding of the definition of an individual act by the scientific community and the legislator is extremely important, as it forms a unified approach to their application. Therefore, the definition of an individual act is proposed.